SCM-49 molecular sieve and preparation method thereof

By preparing SCM-49 molecular sieve with specific chemical composition and structure, the problem of lack of new molecular sieve in the prior art is solved, and its application in gas separation and hydrocarbon conversion reactions is realized, providing new adsorption and catalyst selection.

CN119219021APending Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310781603.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The lack of a new SCM-49 molecular sieve and its preparation method in the prior art limits the development of new gas separation and hydrocarbon conversion reaction applications.

Method used

A SCM-49 molecular sieve is provided with a chemical composition of Al2O3:xSiO2:yP2O5:zCuO, and is crystallized by a crystallization mixture containing an aluminum source, a copper source, a phosphorus source, an organic template agent, a solvent and a selectively added silicon source. Treatment to prepare SCM-49 molecular sieve with specific X-ray diffraction data and nanosheet thickness.

Benefits of technology

The preparation of a new SCM-49 molecular sieve has been realized, with a special X-ray diffraction pattern and nanosheet layer structure, suitable for adsorbents and catalysts, able to separate components in the gas or liquid phase and participate in hydrocarbon reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219021A_ABST
    Figure CN119219021A_ABST
Patent Text Reader

Abstract

The invention discloses an SCM-49 molecular sieve and a preparation method thereof. The molecular sieve comprises the following chemical components in molar ratio: Al2O3: xSiO2: yP2O5: zCuO, x is more than or equal to 0 and less than or equal to 0.5, y is more than or equal to 0.5 and less than or equal to 2.0, and z is more than or equal to 0.2 and less than or equal to 2.0; the molecular sieve has unique X-ray diffraction data. The molecular sieve and the composition thereof can be used as an adsorbent or a catalyst for conversion of organic compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieves, and specifically relates to an SCM-49 molecular sieve and a preparation method thereof. Background Art

[0002] Since the discovery of molecular sieve crystal materials in the 18th century, after several centuries of research and development, this type of material has achieved extraordinary technical results in the fields of adsorption separation, heterogeneous catalysis, carriers of various guest molecules and ion exchange, and has produced a wide range of application bases. Especially with the rapid development of petrochemicals in the 20th century, molecular sieve catalytic materials have become the cornerstone of human production and life. According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), traditional zeolite molecular sieves are a crystalline silicate material, generally composed of silicon-oxygen tetrahedrons [SiO 4 ] 4- and aluminum oxide tetrahedron [AlO 4 ] 5- They are connected by shared oxygen atoms and are collectively referred to as TO 4 Tetrahedron (primary structural unit), in which the silicon element can also be replaced by other elements, especially some trivalent or tetravalent elements such as Al, B, Ga, Ge, Ti, etc. A key factor in determining the application performance of molecular sieves is the characteristics of their pores or cages. The pore diameter of this type of material is generally less than 2nm, and it is classified as microporous materials. In physical and chemical reactions, the substances entering the molecular sieve can be "screened" according to their molecular intrinsic spatial size, so as to carry out corresponding selective adsorption and catalytic shape-selective applications. "Molecular sieve" is named after this. Furthermore, obtaining molecular sieves with new crystal structures is of great significance for the development of molecular sieve applications.

[0003] In 1982, materials scientists ST Wilson and EMFlanigen (US 4310440) of Union Carbide Corporation (UCC) of the United States successfully developed a new family of molecular sieves - aluminum phosphate molecular sieve AlPO using aluminum source, phosphorus source and organic template. 4 -n, n represents the model (including: AlPO 4 -5. AlPO 4 -8. AlPO 4 -9. AlPO 4 -11. AlPO 4 -12. AlPO 4 -14. AlPO 4 -16. AlPO 4 -17. AlPO 4 -18. AlPO 4-20, AlPO 4 -21.AlPO 4 -22. AlPO 4 -23. AlPO 4 -25.AlPO 4 -26.AlPO 4 -28.AlPO 4 -31, etc.), the framework of this type of molecular sieve is made of AlO 4 - and PO 4 + The molecular sieve framework is electrically neutral. Similar to traditional zeolite molecular sieves, the aluminum-oxygen tetrahedron or phosphorus-oxygen tetrahedron in aluminum phosphate molecular sieves can also be replaced by other tetrahedrons. Therefore, UCC has 4 -n, in 1984, Si atoms were used to partially replace Al atoms and P atoms in the aluminum phosphate molecular sieve framework to successfully prepare another series of silicon aluminum phosphate molecular sieves: SAPO-n, where n represents the model (US4440871, US4499327). After the Si atoms in the structure replaced the P and Al atoms in the original AlPO, a SiO 4 、AlO 4 and PO 4 A non-neutral molecular sieve framework composed of tetrahedrons. Among the SAPO-n molecular sieves, it is worth mentioning that the topological structure is the SAPO-34 molecular sieve of CHA, which contains a three-dimensional cross structure of an ellipsoidal supercage and an 8-membered ring channel. The pore size of the 8-membered ring channel is about 0.38nm, and the pore diameter of the supercage is maintained between 0.43 and 0.50nm, because its pore structure has excellent selectivity for low-carbon olefins such as ethylene and propylene, and the appropriate amount of skeleton silicon atoms makes its structure have suitable proton acidity, good thermal stability and good hydrothermal stability. Thanks to this, the SAPO-34 molecular sieve has been successfully commercialized as a catalyst for methanol to low-carbon olefins (MTO) ("Recent Progress in Methanol-to-Olefins (MTO) Catalysts", M. Yang, D. Fan, YX. Wei, P. Tian, ​​ZM. Liu, Adv. Mater. 2019, 1902181).

[0004] So far, most of the known topologically linked aluminum phosphate molecular sieves are prepared by hydrothermal or solvent thermal synthesis. The main steps of a typical hydrothermal or solvent thermal synthesis method are to first mix the reactants such as metal source, non-metal source, organic template, solvent, etc. to obtain an initial crystallization mixture, and then place the crystallization mixture in a reactor lined with polytetrafluoroethylene and stainless steel as the outer wall. After sealing, the crystallization reaction is carried out at a certain temperature and autogenous pressure, imitating the process of mineralization and rock formation on the earth, that is, the process of molecular sieve crystals precipitating from the crystallization mixture. Specifically, taking the synthesis of SAPO-34 molecular sieve as an example, the reaction mixture contains a skeleton reactant (such as silica sol, phosphoric acid and alumina) and a structure directing agent (SDA) and water, and is evenly mixed and placed in a fixed temperature oven (140-220°C) for several days for crystallization reaction. When the crystallization reaction is completed, the solid product containing SAPO-34 molecular sieve is filtered out and dried for use. It is worth mentioning that for the synthesis of aluminum phosphate molecular sieves, the type of organic template is one of the key factors determining its structure, and the presence of organic amine salts is still the most widely used template in the synthesis of aluminum phosphate molecular sieves.

[0005] Up to now, according to the website of the International Molecular Sieve Association (http: / / www.iza-structure.org), including the newly obtained AlPO-91 molecular sieve with ANO topological structure ("Crystalline metallophosphates, their method of preparation, and use", Yuhas, BD, Wilson, KN, Sylejmani-Rekaliu, M., Mowat, JPS, Sinkler, W., US Patent 10,336,622B1 (2019)), there are a total of 248 molecular sieves with different complete and stable topological structures. Although many different crystalline molecular sieves have been obtained, there is still a need for new molecular sieves with desired properties for gas separation and drying, hydrocarbon conversion reactions and other applications. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a new SCM-49 molecular sieve not involved in the prior art and a preparation method thereof.

[0007] The first aspect of the present invention provides a SCM-49 molecular sieve, wherein the molecular sieve comprises a chemical composition having the following molar ratios: Al 2 O 3 :xSiO 2 :yP 2 O 5: zCuO, wherein 0≤x≤0.5, 0.5≤y≤2.0, 0.2≤z≤2.0; the molecular sieve comprises the X-ray diffraction data shown in the following table:

[0008]

[0009]

[0010] Among them, the incident ray of X-ray diffraction is Cu Kα1.

[0011] Furthermore, the SCM-49 molecular sieve also includes X-ray diffraction data as shown in the following table:

[0012] 2θ(°) <![CDATA[Relative intensity, [(I / I 0 )×100]]]> 12.70±0.10 5-50 20.85±0.10 5-50 26.30±0.05 5-50 30.23±0.02 5-50 31.88±0.02 5-50

[0013] Among them, the incident ray of X-ray diffraction is Cu Kα1.

[0014] Furthermore, the SCM-49 molecular sieve also includes X-ray diffraction data as shown in the following table:

[0015] 2θ(°) <![CDATA[Relative intensity, [(I / I 0 )×100]]]> 7.86±0.10 5-50 9.20±0.10 5-50 17.55±0.10 5-50 23.06±0.05 5-50 24.59±0.05 5-50 27.59±0.05 5-50 29.21±0.02 5-50 38.02±0.01 5-50

[0016] Among them, the incident ray of X-ray diffraction is Cu Kα1.

[0017] Furthermore, the thickness of the nanosheets of the SCM-49 molecular sieve is 15 to 30 nm, preferably 10 to 20 nm.

[0018] The second aspect of the present invention provides a method for preparing the above-mentioned SCM-49 molecular sieve, comprising: subjecting a crystallization mixture containing an aluminum source, a copper source, a phosphorus source, an organic template, a solvent and a selectively added silicon source to crystallization treatment to obtain the SCM-49 molecular sieve.

[0019] Furthermore, in the crystallization mixture, Al 2 O 3 Aluminum source as CuO, copper source as SiO 2 Silicon source, P 2 O 5 The molar composition of phosphorus source, organic template and solvent is as follows: SiO 2 / Al 2 O 3 =0 to 1.0, preferably 0.1 to 0.75; and / or, CuO / Al 2 O 3 =0.1 to 2.0, preferably 0.12 to 1.5; and / or, P 2 O 5 / Al 2 O 3=0.5 to 2.0, preferably 0.75 to 1.5; and / or, template / Al 2 O 3 =1 to 200, preferably 5 to 50; and / or, solvent / Al 2 O 3 =10~1000, preferably 50~500.

[0020] Furthermore, the organic template includes template R1 and template R2, and the molar ratio of template R1 to template R2 is (0.01-1):1, preferably (0.1-0.5):1.

[0021] Further, the aluminum source is selected from at least one of aluminum isopropoxide, aluminates, metaaluminates, aluminum hydroxides, aluminum oxides and aluminum-containing minerals; and / or, the copper source is selected from at least one of copper sulfates, nitrates, acetates, copper halides, copper oxides, copper hydroxides and copper-containing minerals; and / or, the silicon source is selected from at least one of organosilicon, solid silicon oxide, silica sol, diatomaceous earth and water glass; and / or, the phosphorus source is selected from at least one of phosphoric acid, monoammonium hydrogen phosphate and diammonium phosphate.

[0022] Further, preferably, the aluminum source is selected from at least one of aluminum isopropoxide, aluminum sulfate, and aluminum nitrate; and / or, the copper source is selected from copper acetate; and / or, the silicon source is selected from at least one of silica sol and solid silicon oxide; and / or, the phosphorus source is selected from orthophosphoric acid.

[0023] Further, the template agent R1 is selected from at least one of tetraethylammonium bromide, tetraethylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetrabutylammonium bromide, and tetrabutylammonium hydroxide; and / or, the template agent R2 is selected from at least one of imidazole, 2-methylimidazole, 4-methylimidazole, 1-(3-aminopropyl)imidazole, 1-isopropylimidazole, N-n-butylimidazole, 2-ethyl-4-methylimidazole, and 1,3-bis(1-adamantyl)imidazole hydroxide.

[0024] Further, preferably, the template agent R1 is selected from at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide; and / or, the template agent R2 is selected from at least one of 1-(3-aminopropyl)imidazole, 1-isopropylimidazole and 2-ethyl-4-methylimidazole.

[0025] Further, preferably, the template agent R1 is selected from tetraethylammonium hydroxide; and / or, the template agent R2 is selected from 1-(3-aminopropyl)imidazole.

[0026] Furthermore, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N,N-dibutylformamide, ethanol, ethylene glycol, butanol and water.

[0027] Further, preferably, the solvent is selected from deionized water.

[0028] Furthermore, the conditions of the crystallization treatment include: a crystallization temperature of 120 to 200° C., preferably 140 to 180° C., more preferably 140 to 160° C.; and / or a crystallization time of 1 to 5 days, preferably 3 to 5 days.

[0029] Furthermore, in the preparation method, stirring and precipitation treatments are performed before crystallization treatment.

[0030] Furthermore, the stirring treatment time is 1 to 12 hours, and the sedimentation treatment time is 1 to 12 hours.

[0031] Furthermore, after the precipitation, heat treatment may be performed to obtain a crystallized mixture.

[0032] Furthermore, the heat treatment temperature is 80°C to 120°C, and the time is 1 to 12 hours.

[0033] Furthermore, the method performs conventional post-treatment after crystallization, such as filtering, washing, and drying to obtain SCM-49 molecular sieve. Preferably, the drying temperature is 90 to 120° C. and the drying time is 0.5 to 10 hours. And optionally, a step of calcining the obtained molecular sieve is performed.

[0034] Furthermore, preferably, the template agent is composed of template agent R1 and template agent R2, the template agent R1 is tetraethylammonium hydroxide, and the template agent R2 is 1-(3-aminopropyl)imidazole; the solvent is water; the crystallization mixture is crystallized at 140-160° C. for 3-5 days, and the product is filtered, washed, and dried at 90-120° C. to obtain SCM-49 molecular sieve.

[0035] The SCM-49 molecular sieve provided by the present invention may contain a certain amount of water after synthesis, but the amount of water is not necessarily limited in the present invention, and the presence or absence of the water does not substantially affect the XRD spectrum of the molecular sieve.

[0036] The SCM-49 molecular sieve provided by the present invention can be used in any physical form, such as powder, granule or molded product (such as strip, clover, etc.). These physical forms can be obtained in any conventional manner known in the art without particular limitation.

[0037] The present invention also provides a molecular sieve composition, comprising the above-mentioned SCM-49 molecular sieve or the SCM-49 molecular sieve prepared according to the preparation method of the SCM-49 molecular sieve. The other materials contained in the molecular sieve composition can be active materials and inactive materials. As the active material, it can be other molecular sieves, and as the inactive material (generally referred to as a binder), it can be clay, alumina, silica gel, etc. These other materials can be used alone or in combination in any proportion. As the amount of the other materials, the conventional amount used in the art can be referred to, and there is no particular limitation.

[0038] The SCM-49 molecular sieve provided by the present invention, the SCM-49 molecular sieve prepared by the method for preparing the SCM-49 molecular sieve, or the molecular sieve composition can be used as an adsorbent or a catalyst.

[0039] The SCM-49 molecular sieve or molecular sieve composition of the present invention can be used as an adsorbent, for example, to separate at least one component from a mixture of multiple components in a gas phase or a liquid phase. Accordingly, the at least one component can be partially or substantially completely separated from the mixture of various components, for example, by contacting the mixture with the SCM-49 molecular sieve or the molecular sieve composition to selectively adsorb the component.

[0040] According to one aspect of the present invention, the molecular sieve SCM-49 or the molecular sieve composition can also be used as a catalyst (or as its catalytically active component) directly or after necessary treatment or conversion (such as ion exchange, etc.) conventionally performed on the molecular sieve in the art. To this end, according to one aspect of the present invention, for example, reactants (such as hydrocarbons) can be subjected to a predetermined reaction in the presence of the catalyst, and the target product can be obtained thereby. Among them, the predetermined reaction can be exemplified as follows: methanol conversion, synthesis gas to hydrocarbons, olefin cracking, olefin disproportionation and isopropylbenzene cracking and other reactions.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The SCM-49 molecular sieve of the present invention is a new type of molecular sieve never obtained before in the art and has a special X-ray diffraction pattern. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The XRD diffraction spectrum of the molecular sieve prepared in Example 1;

[0044] Figure 2 This is a SEM photograph of the molecular sieve prepared in Example 1. DETAILED DESCRIPTION

[0045] The following examples will further illustrate the technical solutions provided by the present invention, but the protection scope of the present invention is not limited by these examples.

[0046] In the present invention, the structure of the molecular sieve is determined by an X-ray diffraction spectrum (XRD), and the X-ray diffraction spectrum (XRD) of the molecular sieve is measured by an X-ray powder diffractometer using a Cu-Kα ray source with a Kα1 wavelength. Nickel filter. The X'Pert PRO X-ray powder diffraction (XRD) instrument used was from PANalytical of the Netherlands, with an operating voltage of 40 kV, a current of 40 mA, and a scanning range of 3.0 to 50°.

[0047] In the present invention, the morphology of the molecular sieve is photographed using a S-4800 field emission scanning electron microscope (Fe-SEM) produced by Japan HITACHI Corporation.

[0048] [Example 1]

[0049] Take 102.1 g of aluminum isopropoxide (Al(iPr) 3 ) was dissolved in 4246.2 mL of deionized water and mixed to form solution A. Then, 99.8 g of cupric acetate (monohydrate), 43.2 g of phosphoric acid (purity ≥ 85 wt.%), 294.6 g of tetraethylammonium hydroxide (50 wt.% aqueous solution) and 500.7 g of 1-(3-aminopropyl)imidazole (≥ 98%) were added to solution A. After stirring for 8 h and settling for 5 h, solution B was obtained. Then, 45 g of white carbon black (≥ 99%) was slowly added to solution B. After stirring for 4 h, the mixture was heat treated at 110 ° C for 3 h to form a uniform crystallized mixture. 2 O 3 Aluminum source in terms of CuO, copper source in terms of SiO 2 Silicon source, P 2 O 5 The molar ratio of phosphorus source, template and solvent is: Al 2 O 3 :CuO:SiO 2 :P 2 O 5 :Template R:Solvent S=1:0.5:0.75:0.75:5:250,Template R1(tetraethylammonium hydroxide) / Template R2(1-(3-aminopropyl)imidazole)=0.25,The above crystallization mixture was placed at 140℃ for crystallization for 5d,The product was filtered and washed and then dried at 90℃ for 10h to obtain the product SCM-49,The components in the molecular sieve after drying the sample were measured by inductively coupled plasma atomic emission spectroscopy (ICP) as Al 2 O 3 :0.4SiO2 :0.8P 2 O 5 :0.6CuO. Its X-ray diffraction pattern is shown in Table 1 and Figure 1 The obtained SCM-49 morphology is shown in Figure 2 ,pass Figure 2 It can be seen that the nanosheet layer is relatively thin, with a thickness of 10 to 20 nm.

[0050] Table 1

[0051]

[0052]

[0053] [Example 2]

[0054] 375.1 g of aluminum nitrate [Al(NO 3 ) 3 9H 2 O] was dissolved in 651.0 mL of water and mixed to form solution A. Then, 599.0 g of cupric acetate (monohydrate), 115.3 g of phosphoric acid (purity ≥ 85 wt.%), 1483.3 g of tetraethylammonium hydroxide (25 wt.% aqueous solution) and 2188.0 g of 1-(3-aminopropyl)imidazole (≥ 98%) were added to solution A. After stirring for 10 h and settling for 3 h, solution B was obtained. Then, 32.0 g of acidic silica sol (40 wt.% aqueous solution) was slowly added to solution B. After stirring for 2.5 h, the mixture was heat treated at 100 ° C for 6 h to form a uniform crystallized mixture, wherein Al 2 O 3 Aluminum source in terms of CuO, copper source in terms of SiO 2 Silicon source, P 2 O 5 The molar ratio of phosphorus source, template and solvent is: Al 2 O 3 :CuO:SiO 2 :P 2 O 5 :Template R:Solvent S=1:1.5:0.1:1.5:10:50,Template R1 (tetraethylammonium hydroxide) / Template R2 (1-(3-aminopropyl)imidazole)=0.14,The above crystallization mixture was placed at 140℃ for crystallization for 4d,The product was filtered and washed and then dried at 120℃ for 5h to obtain the product SCM-49,The components in the molecular sieve after drying the sample were measured by inductively coupled plasma atomic emission spectroscopy (ICP) in terms of molar ratio of Al 2 O 3 :0.08SiO 2 :1.5P 2 O 5:1.6CuO. Its X-ray diffraction lines are shown in Table 2. The SEM images of the samples are Figure 2 Similarly, the nanosheet layer is thin, with a nanosheet thickness of 10 to 20 nm.

[0055] Table 2

[0056]

[0057]

[0058] [Example 3]

[0059] 2.0 g of aluminum isopropoxide was dissolved in 19.8 mL of water and mixed to form solution A. Then, 4.0 g of copper acetate (monohydrate), 1.2 g of phosphoric acid (purity ≥ 85 wt.%), 68.0 g of tetraethylammonium hydroxide (50 wt.% aqueous solution) and 96.4 g of 1-(3-aminopropyl)imidazole (≥ 98%) were added to solution A. After stirring for 6 h and settling for 7 h, solution B was obtained. Then, 0.6 g of white carbon black (≥ 99%) was slowly added to solution B. After stirring for 4.5 h, the mixture was heat treated at 80 ° C for 12 h to form a uniform crystallized mixture, wherein Al 2 O 3 Aluminum source in terms of CuO, copper source in terms of SiO 2 Silicon source, P 2 O 5 The molar ratio of phosphorus source, template and solvent is: Al 2 O 3 :CuO:SiO 2 :P 2 O 5 :Template R:Solvent S=1:1:0.5:1:50:150,Template R1 (tetraethylammonium hydroxide) / Template R2 (1-(3-aminopropyl)imidazole)=0.3,The above crystallization mixture was placed at 140℃ for crystallization for 3d,The product was filtered and washed and then dried at 100℃ for 8h to obtain the product SCM-49,The components in the molecular sieve after drying the sample were measured by inductively coupled plasma atomic emission spectroscopy (ICP) in terms of molar ratio of Al 2 O 3 :0.4SiO 2 :1.0P 2 O 5 :1.1CuO. Its X-ray diffraction lines are shown in Table 3. The SEM images of the samples are Figure 2 Similarly, the nanosheet layer is thin, with a nanosheet thickness of 10 to 20 nm.

[0060] Table 3

[0061] 2θ(°) <![CDATA[Relative intensity, [(I / I 0 )×100]]]> 5.66 100 6.65 55 7.86 16 9.22 8 12.73 5 13.70 18 17.59 27 18.41 40 20.86 15 22.56 26 23.11 5 24.60 22 26.33 19 27.57 12 28.15 5 29.22 9 30.23 16 31.89 9 34.05 10 38.02 8

[0062] [Example 4]

[0063] 3332.1 g of aluminum sulfate was dissolved in 60271.2 mL of water and mixed to form solution A. Then, 2395.8 g of copper acetate (monohydrate), 691.8 g of phosphoric acid (purity ≥ 85 wt.%), 32988.3 g of tetraethylammonium hydroxide (25 wt.% aqueous solution) and 34275.2 g of 1-(3-aminopropyl)imidazole were added to solution A. After stirring for 4 h and settling for 9 h, solution B was obtained. Then, 640.0 g of acidic silica sol (40 wt.% aqueous solution) was slowly added to solution B. After stirring for 3.5 h, the mixture was heat treated at 90 ° C for 8 h to form a uniform crystallized mixture, wherein Al 2 O 3 Aluminum source in terms of CuO, copper source in terms of SiO 2 Silicon source, P 2 O 5 The molar ratio of phosphorus source, template and solvent is: Al 2 O 3 :CuO:SiO 2 :P 2 O 5 :Template R:Solvent S=1:1.2:0.4:1.2:33:475,Template R1(tetraethylammonium hydroxide) / Template R2(1-(3-aminopropyl)imidazole)=0.2,The above crystallization mixture was placed at 140℃ for crystallization for 5d,The product was filtered and washed and then dried at 110℃ for 6h to obtain the product SCM-49,The components in the molecular sieve after drying the sample were measured by inductively coupled plasma atomic emission spectroscopy (ICP) in terms of molar ratio of Al 2 O 3 :0.3SiO 2 :1.3P 2 O 5 :1.2CuO. Its X-ray diffraction lines are shown in Table 4. The SEM images of the samples are Figure 2 Similarly, the nanosheet layer is thin, with a nanosheet thickness of 10 to 20 nm.

[0064] Table 4

[0065] 2θ(°) <![CDATA[Relative intensity, [(I / I 0 )×100]]]> 5.55 100 6.44 88 7.80 26 9.10 5 12.60 25 13.54 17 17.50 33 18.31 18 20.77 5 22.56 6 23.01 20 24.56 22 26.28 19 27.59 15 28.13 35 29.20 8 30.23 5 31.87 9 34.02 20 38.00 5

[0066] [Example 5]

[0067] 20.4 g of aluminum isopropoxide was dissolved in 248.9 mL of water and mixed to form solution A. Then, 5.6 g of copper acetate (monohydrate), 12.7 g of phosphoric acid (purity ≥ 85 wt.%), 788.6 g of tetraethylammonium hydroxide (50 wt.% aqueous solution) and 670.9 g of 1-(3-aminopropyl)imidazole were added to solution A. After stirring for 3 h and settling for 10 h, solution B was obtained. Then, 4.8 g of acidic silica sol (40 wt.% aqueous solution) was slowly added to solution B. After stirring for 1.5 h, the mixture was heat treated at 90 ° C for 11 h to form a uniform crystallized mixture, wherein Al 2 O 3 Aluminum source in terms of CuO, copper source in terms of SiO 2 Silicon source, P 2 O 5 The molar ratio of phosphorus source, template and solvent is: Al 2 O 3 :CuO:SiO 2 :P 2 O 5 :Template R:Solvent S=1:0.14:0.16:1.1:39.8:180,Template R1 (tetraethylammonium hydroxide) / Template R2 (1-(3-aminopropyl)imidazole)=0.5,The above crystallization mixture was placed at 140℃ for crystallization for 3d,The product was filtered and washed and then dried at 100℃ for 8h to obtain the product SCM-49,The components in the molecular sieve after drying the sample were measured by inductively coupled plasma atomic emission spectroscopy (ICP) in terms of molar ratio of Al 2 O 3 :0.1SiO 2 :1.2P 2 O 5 :0.23CuO. The data of its X-ray diffraction line are shown in Table 5. The SEM image of the sample is Figure 2 Similarly, the nanosheet layer is thin, with a nanosheet thickness of 10 to 20 nm.

[0068] Table 5

[0069]

[0070]

[0071] [Example 6]

[0072] 102.1 g of aluminum isopropoxide was dissolved in 13370.6 g of N,N-dimethylformamide (DMF) and mixed to form solution A. Then, 30.0 g of copper sulfate (pentahydrate), 63.4 g of phosphoric acid (purity ≥ 85 wt.%), 2082.3 g of tetrapropylammonium hydroxide (50 wt.% aqueous solution) and 1881.0 g of 1-isopropylimidazole were added to solution A. After stirring for 3 h and settling for 10 h, solution B was obtained. Then, 90.0 g of acidic silica sol (40 wt.% aqueous solution) was slowly added to solution B. After stirring for 1.5 h, the mixture was heat treated at 90 ° C for 1 h to form a uniform crystallized mixture, wherein Al 2 O 3 Aluminum source in terms of CuO, copper source in terms of SiO 2 Silicon source, P 2 O 5 The molar ratio of phosphorus source, template and solvent is: Al 2 O 3 :CuO:SiO 2 :P 2 O 5 :Template R:Solvent S=1:0.12:0.6:1.1:22.2:244,Template R1 (tetrapropylammonium hydroxide) / Template R2 (1-isopropylimidazole)=0.3,The above crystallization mixture was placed at 160℃ for crystallization for 3d,The product was filtered and washed and then dried at 100℃ for 8h to obtain the product SCM-49,The components in the molecular sieve after drying the sample were measured by inductively coupled plasma atomic emission spectroscopy (ICP) in terms of molar ratio of Al 2 O 3 :0.5SiO 2 :1.25P 2 O 5 :0.2CuO. The data of its X-ray diffraction line are shown in Table 6. The SEM picture of the sample is Figure 2 Similarly, the nanosheet layer is thinner, with a nanosheet thickness of 15 to 20 nm.

[0073] Table 6

[0074]

[0075]

[0076] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A SCM-49 molecular sieve, comprising a chemical composition having the following molar ratio: Al2O3:xSiO2:yP2O5:zCuO, wherein 0≤x≤0.5, 0.5≤y≤2.0, 0.2≤z≤2.0; the molecular sieve comprises X-ray diffraction data as shown in the following table: in, The incident ray for X-ray diffraction is Cu Kα1.

2. The molecular sieve according to claim 1, characterized in that The SCM-49 molecular sieve also includes X-ray diffraction data as shown in the following table: Among them, the incident ray of X-ray diffraction is Cu Kα1.

3. The molecular sieve according to claim 1 or 2, characterized in that: The SCM-49 molecular sieve also includes X-ray diffraction data as shown in the following table: Among them, the incident ray of X-ray diffraction is Cu Kα1.

4. The molecular sieve according to claim 1, characterized in that The thickness of the nanosheet of the SCM-49 molecular sieve is 15 to 30 nm.

5. The method for preparing the molecular sieve according to any one of claims 1 to 4, comprising: A crystallization mixture containing an aluminum source, a copper source, a phosphorus source, an organic template, a solvent and a selectively added silicon source is crystallized to obtain a SCM-49 molecular sieve.

6. The preparation method according to claim 5, characterized in that: In the crystallization mixture, the molar compositions of the aluminum source calculated as Al2O3, the copper source calculated as CuO, the silicon source calculated as SiO2, the phosphorus source calculated as P2O5, the organic template and the solvent are as follows: SiO2 / Al2O3=0~1.0, preferably 0.1~0.75; and / or, CuO / Al2O3=0.1~2.0, preferably 0.12~1.5; and / or, P2O5 / Al2O3=0.5~2.0, preferably 0.75~1.5; and / or, template / Al2O3=1~200, preferably 5~50; and / or, solvent / Al2O3=10~1000, preferably 50~500.

7. The preparation method according to claim 5, characterized in that: The organic template includes template R1 and template R2, and the molar ratio of template R1 to template R2 is (0.01-1):

1.

8. The preparation method according to claim 5, characterized in that: The aluminum source is selected from at least one of aluminum isopropoxide, aluminates, metaaluminates, aluminum hydroxides, aluminum oxides and aluminum-containing minerals; and / or, the copper source is selected from at least one of copper sulfates, nitrates, acetates, copper halides, copper oxides, copper hydroxides and copper-containing minerals; and / or, the silicon source is selected from at least one of organosilicon, solid silicon oxide, silica sol, diatomaceous earth and water glass; and / or, the phosphorus source is selected from at least one of phosphoric acid, monoammonium hydrogen phosphate and diammonium phosphate.

9. The preparation method according to claim 7, characterized in that: The template agent R1 is selected from at least one of tetraethylammonium bromide, tetraethylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetrabutylammonium bromide, and tetrabutylammonium hydroxide; and / or, the template agent R2 is selected from at least one of imidazole, 2-methylimidazole, 4-methylimidazole, 1-(3-aminopropyl)imidazole, 1-isopropylimidazole, N-n-butylimidazole, 2-ethyl-4-methylimidazole, and 1,3-bis(1-adamantyl)imidazole hydroxide.

10. The preparation method according to claim 5, characterized in that: The conditions of the crystallization treatment include: a crystallization temperature of 120 to 200° C.; and / or a crystallization time of 1 to 5 days.

11. A molecular sieve composition, characterized in that: The invention comprises the molecular sieve according to any one of claims 1 to 4 or the molecular sieve prepared according to any one of claims 5 to 10, and a binder.

12. Use of the molecular sieve according to any one of claims 1 to 4, or the molecular sieve prepared according to the method according to any one of claims 5 to 10, or the molecular sieve composition according to claim 11 in an adsorbent or catalyst.